Intertwining Tongues：Bilingualism and Hybrid Texts in Contemporary Japanese Literature ―― From I am a Cat to I Become a Cat - Faye Yuan Kleeman (Gwagyeong Ilboneo Munhak Yeongu, 2018)
The study of Japanophone literature (Nihongo bungaku) has recently emerged as a new area within Japanese literary studies. Scholars consider the category as part of the legacy of Japan’s colonial language policy and often focus on its subversive and productive possibilities in revealing the asymmetrical dynamics of languages and facilitating the expansion of the scope of Japanese literature. One of the features of Nihongo bungaku is its bilingual textual elements and the authors’ bifocal cultural rendering of the text. This article builds on the notion that all translated texts are hybrid texts (Schaffner and Adab, 2001) and seeks to explore the potential for Japanese writers to participate in the production of Nihongo bungaku, in particular in the milieu of Sino-Japanese literary interactions. It first considers issues of bilingualism and diglossia and the historical kanji-kana graphic interface, asking whether the mixed graphic system fits into a scheme of (non) translation. Finally, the paper discusses the recent bilingual novel I Became a Cat by Yokoyama Yūta to examine his use of lexical innovation, textual hybridity, and parody. I seek to demonstrate that Yokoyama’s playful gestures toward translation, transliteration, and bilingual and translingual praxis relocate Sōseki’s canonical work out of the Meiji domestic environment and turn it into a bi-cultural global text.